Dirac’s Variable Gravitational Parameter G Offers a Link Between Gravity and Quantum Mechanics - Eriksson, Jarl-Thure (European Journal of Applied Sciences, 2024)
The Standard model has successfully depicted the universe from a tremendous number of astronomical observations. However, the model faces several problems, it does not provide theoretical explanations for the origin of the Big Bang, dark energy or dark matter. The theory behind this article, CBU for Continuously Breeding Universe, was developed according to known principles of physics. The universe is an emerging system, which starts from the single fluctuation of a positron-electron pair. Expansion is driven by the emersion of new pairs. The gravitational parameter G is inversely proportional to the Einsteinian curvature radius r. The Planck length and Planck energy WP are dependent of the curvature and accordingly by the size of the universe. As a measure of the change of the state between a stationary body (G0) and a moving body (G1) the ratio G1/G0 unites the Special theory with the General theory of relativity. Relativity means that the motion of a body always is relative to another body according to the ratio of their G values. The introduction of different individual Gs implies symmetry in the twin paradox, leading to the first credible solution to the problem.